NGS transcriptomic analysis uncovers the possible resistance mechanisms of olive to Spilocea oleagina leaf spot infection - Marchese, Annalisa; Balan, Bipin; Trippa, Daniela Antonina; Bonanno, Floriana; Caruso, Tiziano; Imperiale, Valeria; Marra, Francesco Paolo; Giovino, Antonio (Frontiers in Plant Science, 2023)
Spilocea oleagina is a dangerous obligate fungal pathogen of olive, feared in the Mediterranean countries, causing Peacock’s eye or leaf spot infection that can lead to a serious yield loss of about 20% or higher depending on climatic conditions. Coping with this disease is much more problematic in organic farms. So far, the knowledge of the genetic control of possible mechanisms of resistance/low susceptibility is quite limited. In this work, comparative transcriptomic analysis (RNA-seq) was conducted in leaf tissues of a low susceptible cultivar Koroneiki and a high susceptible cultivar Nocellara del Belice, both tested in the field using the NaOH test, considering two stages – “zero sign of disease” and “evident sign of infection”. Cultivars showed a very large number of differentially expressed genes (DEGs) in both stages. ‘Koroneiki’ showed an extensive hormonal crosstalk, involving Abscisic acid (ABA) and ethylene synergistically acting with Jasmonate, early signaling of the disease and remarkable defense responses against Spilocea, through the over-expression of many resistance gene analogs or pathogenesis-related (PR) genes: non-specific lipid-transfer genes (nsLTPs), LRR receptor-like serine/threonine-protein kinase genes, GDSL esterase lipase, defensin Ec-AMP-D2-like, pathogenesis-related leaf protein 6-like, Thaumatin-like gene, Mildew resistance Locus O (MLO) gene, glycine-rich protein (GRP), MADS-box genes, STH-21-like, endochitinases, glucan endo-1,3-beta-glucosidases and finally many proteinases. Numerous genes involved in cell wall biogenesis, remodeling, and cell wall-based defense, including lignin synthesis, were also up-regulated in the resistant cultivar, indicating the possible role of wall composition on disease resistance. It was remarkable that many transcription factors (TS), some of which involved in Induced Systemic Resistance (ISR), as well as some also involved in abiotic stress response, were found uniquely expressed in ‘Koroneiki’, while ‘Nocellara del Belice’ was lacking an effective system of defense, expressing genes that overlap with wounding responses, and in minor extent genes related to phenylpropanoid and terpenoid pathways. Only a Thaumatin-like gene was found in both cultivars showing a similar expression. In this work, the genetic factors and mechanism underlying the putative resistance trait against this fungal pathogen were unraveled for the first time and possible target genes for breeding resistant olive genotypes were found.